Shared Experience of Reading Literature with Adult Language Learners - Parente-Čapková Viola (Charles University in Prague, Faculty of Arts, Institute of Czech and Comparative Literature, 2025)
Reading experience has been researched and defined, in various ways and contexts, as an emotional, intellectual, or even physical event. The role of language in reading experience has been recognized, but the way reading experience is connected to language acquisition and plays the role of a formative experience has not been dealt with in literary studies. In this article, I reflect on the shared reading experience of adult learners of Finnish with academic backgrounds in reading circles organized by the research project Struck by the Unknown: Fiction as Promoter of the Finnish Language among Adults with Im/migrant Background. In the reading experience as this is connected to cultural language learning in a reading circle, it is impossible to separate cognitive processes and emotions from the intellectual event. An appropriate venue to explore the cognitive, emotional, and intellectual together is a reading circle, where aesthetic experience permeates a learning process. I will bring up some facets of shared reading as experience formation by reporting on how our research team and reading circle participants experienced the project. Facets of this shared experience of reading include a dialogical transborder approach that creates space to articulate emotions. Finally, I reflect briefly on the issue of using or instrumentalizing literature.